Revisión de la literatura: consecuencias del uso del formocresol en el tratamiento de momificación y la tasa de éxito de los materiales usados en pulpotomias (2020)
For more than 30 years, formocresol has generated controversy due to adverse effects, for this reason reason a systematic review is performed to determine whether during treatment of mummification in deciduous teeth the use of formocresol generates carcinogenic effects and cytotoxic in the human body, and the effectiveness of other materials compared to Formocresol for mummification treatment. A database is created with 178 articles and documents downloaded, 17 were excluded and 123 qualified for the systematic review of the literature, they are tabulated by year and the information required by each document for the development of the work. During the review, collects information on pulpotomy, materials used for treatment of pulpotomies, the use of formocresol, in vivo and invitro studies that have been carried out to determine if it generates toxicity, carcinogenic effects or any alteration. During the analysis, information was collected of 37 studies comparing the clinical and radiographic effectiveness of ferric sulfate, glutaraldehyde, sodium hypochlorite, calcium hydroxide and MTA against formocresol. The added mineral trioxide agent and Biodentine are the ideal materials to replace the formocresol in mummification treatments, and calcium hydroxide the least indicated already that generates internal resorption in deciduous teeth, there is not enough evidence to confirm the hypothesis that formocresol causes cancer-causing and mutagenic changes in cells due to biases in each research study, but formaldehyde being the main component of formocresol is attributed to the toxic effects generated in dental tissues and adjacent to the application site.